A local perspective on renewable energy development in the Russian Arctic - Gritsenko, Daria; Salonen, Hilma (Elementa: Science of the Anthropocene, 2022)
Many Arctic communities are exposed to energy security risks. Remote settlements rely largely on diesel for energy production, which results in higher consumer prices, negative impacts on the environment and public health. In the past few years, pilot projects for switching remote villages from diesel-generated to wind- and solar-diesel hybrid power plants were realized across the Arctic. Renewable energy projects have a major potential to alleviate energy security risks, promote public health and better environment. Yet, renewable energy does not take hold easily in the Arctic region. Especially in Russia, significant subsidies for fossil fuel present a major disincentive, as well as perpetuate vested interests of national oil companies. Despite the Russian Arctic being a ‘hard case’ for renewables development, there has been both interest in and progress towards the uptake of renewable energy across the Russian Arctic regions. This article contributes to the ‘local turn’ in sustainable energy policy studies by exploring two intertwined questions: which factors contribute to renewable energy development in the Russian Arctic and how do these factors characterise differences between individual Arctic communities? Using a combination of exploratory factor analysis and correspondence analysis in application to the local level (municipal) data, we update the existing models of the factors contributing to renewable energy uptake and put forward four distinct community-level models that describe renewables uptake. We conclude by emphasizing the importance of the local perspective on sustainable energy as a key to explaining differences in observed policy outcomes. Peer reviewed